Modelling cadmium‐induced cardiotoxicity using human pluripotent stem cell‐derived cardiomyocytes. Issue 9 (11th July 2018) - Shen, Jiaxi; Wang, Xiaochen; Zhou, Danni; Li, Tongyu; Tang, Ling; Gong, Tingyu; Su, Jun; Liang, Ping
Abstract: Cadmium, a highly ubiquitous toxic heavy metal, has been widely recognized as an environmental and industrial pollutant, which confers serious threats to human health. The molecular mechanisms of the cadmium‐induced cardiotoxicity (CIC) have not been studied in human cardiomyocytes at the cellular level. Here we showed that human pluripotent stem cell‐derived cardiomyocytes (hPSC‐CMs) can recapitulate the CIC at the cellular level. The cadmium‐treated hPSC‐CMs exhibited cellular phenotype including reduced cell viability, increased apoptosis, cardiac sarcomeric disorganization, elevated reactive oxygen species, altered action potential profile and cardiac arrhythmias. RNA‐sequencing analysis revealed a differential transcriptome profile and activated MAPK signalling pathway in cadmium‐treated hPSC‐CMs, and suppression of P38 MAPK but not ERK MAPK or JNK MAPK rescued CIC phenotype. We further identified that suppression of PI3K/Akt signalling pathway is sufficient to reverse the CIC phenotype, which may play an important role in CIC. Taken together, our data indicate that hPSC‐CMs can serve as a suitable model for the exploration of molecular mechanisms underlying CIC and for the discovery of CIC cardioprotective drugs.